2022
DOI: 10.1002/pssb.202200064
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Co Content and Temperature on Shear Mechanical Properties of Nano‐Polycrystalline Ni–Co Alloy

Abstract: Herein, the effects of different Co content and temperature factors on the shear mechanical properties of nano‐polycrystalline nickel–cobalt alloy are analyzed by molecular dynamics (MD) simulations. It is found in the work that the highest shear modulus of 63.03 GPa is obtained when the Co content is 10%, attributed to the lattice distortion caused by the difference in the lattice parameters between two elements. During the shearing process, the multilevel twins are present with intensification of the deforma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Hua et al [29] employed MD methods to study the shear mechanical properties of graphene/ copper composites and discovered that the incorporation of graphene significantly enhances the shear strength of the composite material. Chen et al [30] conducted MD simulations on the effects of varying Co content and temperature on the shear mechanical properties of Ni-Co alloys and found that the incorporation of Co atoms into pure Ni causes lattice distortion, increasing the resistance to dislocation motion and thereby enhancing the material's strength. Chang et al [31] utilized MD simulations to investigate the impact of grain size, temperature, and gradient Al content on the deformation mechanism of Ni 50-x Ti 50 Al x polycrystalline alloys, identifying the content of Al atoms and temperature as primary factors affecting the material's failure mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Hua et al [29] employed MD methods to study the shear mechanical properties of graphene/ copper composites and discovered that the incorporation of graphene significantly enhances the shear strength of the composite material. Chen et al [30] conducted MD simulations on the effects of varying Co content and temperature on the shear mechanical properties of Ni-Co alloys and found that the incorporation of Co atoms into pure Ni causes lattice distortion, increasing the resistance to dislocation motion and thereby enhancing the material's strength. Chang et al [31] utilized MD simulations to investigate the impact of grain size, temperature, and gradient Al content on the deformation mechanism of Ni 50-x Ti 50 Al x polycrystalline alloys, identifying the content of Al atoms and temperature as primary factors affecting the material's failure mechanism.…”
Section: Introductionmentioning
confidence: 99%